KEANEKARAGAMAN JENIS VEGETASI TEPIAN SUNGAI KAILI DESA LABUAN KUNGGUMA KECAMATAN LABUAN - Lahusen, Moh. Rafli; Naharuddin, Naharuddin; Sustri, Sustri (Jurnal Warta Rimba, 2014)
Kaili watershed aims to be a regulator of water system that has important role for society. This experiment employed systematic strip plot sampling method. It also aims to find out the species of the edge of tree vegetation varieties at Kaili river of Labuan Kungguma Village in Labuan Sub-district. Based on the observation on tree level, in Kaili river, the most dominating is Dracontomelon dao (Blanco) Merr. & Rolfe., tree which has IVI 32.19%. At the level of pole tree, it is dominated by Dracontomelon dao (Blanco) Merr. & Rolfe., which has IVI 29.71% of its important Index Value. At the level of stake, it is dominated by Magnolia champaca, which has IVI 19.42%. At the level of undergrowth, it is dominated by Thallophyta, which has IVI 14.47%. The level of this species varieties classified into high criteria. The level of species diversity (H’) at the level of tree reached 3.08% and it is classified into high criteria; at the pole level which reached 2.84% classified into moderate criteria; at the level of stake reached 3.27% classified into high criteria; and at undergrowth level reached 3.39% classified into high criteria. Keywords : Kaili River, diversity, vegetation.